Site-specific agronomic information and technology adoption: A field experiment from Ethiopia - Newman, Carol (My University, 2022)
Smallholder farmers in Africa typically only have access to blanket fertilizer recommendations which are defined over very broad areas and may not be optimal for local production conditions. The response to such recommendations has generally been poor. Using a randomized control trial in Ethiopia, we explore whether targeted extension advice leads farmers to align fertilizer usage to the recommended levels and whether this impacts productivity. We also consider whether coupling the targeted information with agricultural insurance encourages fertilizer investment. Results show that targeted recommendations closed the gap between the amount of fertilizer used and the recommended amounts and this in turn increased productivity and profits. We found no differential effect of the targeted recommendation when coupled with agricultural insurance, suggesting that the risk of crop failure is not a binding constraint to fertilizer adoption in this context, or that farmers do not consider agricultural insurance a useful risk-mitigating mechanism.
PUBLISHED
Keywords: Digital agriculture; Agriculture; Fertilizer; Agricultural extension; Advisory services; Smallholder agriculture; International Development; AGRICULTURAL ECONOMICS; Development Economics; RANDOMIZED CONTROLLED TRIAL